THE RELATIONSHIP BETWEEN WORKING FROM HOME AND EMPLOYEE PERFORMANCE: THE ROLE OF FAMILY CLIMATE AS A MODERATING VARIABLE - Khurin Aini; Faiz Fatihul ‘Alwan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the relationship between Work From Home (WFH) and employee performance and confirms the role of family climate as a moderating variable. The method used is quantitative correlational, involving 206 respondents who work from home. The results of Moderated Regression Analysis show that WFH is significantly related to performance (β = 0.69191; p < 0.001), family climate is also significantly related to performance (β = 0.20040; p < 0.001), and family climate significantly moderates the relationship between WFH and performance (β = 0.00443; p = 0.0038), confirming that the quality of family climate can strengthen the relationship between the two. These findings indicate that the effectiveness of WFH is not only influenced by the work itself, but also highly dependent on family conditions at home.